EFFICACY OF HISTAMINE H2-RECEPTOR BLOCKERS IN CHILDREN WITH NEPHROTIC SYNDROME RECEIVING GLUCOCORTICOSTEROID THERAPY - Самадов Абдукаххор Абдурахмонович; Нурматова Наргиза Фахтуллаевна; Хабибуллоева Бибирозия Рахматуллозода (European Journal of Interdisciplinary Research and Development, 2023)
Clinical and laboratory studies were conducted in 46 children from 12 to 18 years of age. Of these, there were 30 girls and 16 boys. All children received glucocorticosteroid therapy for nephrotic syndrome. According to the results of esophagogastroduodenoscopy, all children had lesions of the gastroduodenal zone. 1 group of patients was prescribed a drug from the group of histamine H2-receptor blockers - ranitidine 300 mg. After therapy, 85% of group 1 children were found to have eradication of erosive lesions of the gastroduodenal zone